Erinnerungsorte in der Musik - Jaszoltowski, Saskia (De Gruyter, 2022)
Why do we remember certain music from the past and attribute meaning to it, while other protagonists from the history of music slip into obscurity? Armed with this question, the author embarks upon a journey to sites of memory in music, visiting Beethoven's Ninth Symphony, the Rock and Roll Hall of Fame, Mozart and Graz, the genre of hip hop, the philharmonic and the Jewish Museum in Berlin.